2016
DOI: 10.3171/2016.2.spine15954
|View full text |Cite
|
Sign up to set email alerts
|

Costs and readmission rates for the resection of primary and metastatic spinal tumors: a comparative analysis of 181 patients

Abstract: OBJECTIVE Because the surgical strategies for primary and metastatic spinal tumors are different, the respective associated costs and morbidities associated with those treatments likely vary. This study compares the direct costs and 90-day readmission rates between the resection of extradural metastatic and primary spinal tumors. The factors associated with cost and readmission are identified. METHODS Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 44 publications
(63 reference statements)
5
39
2
Order By: Relevance
“…24,25 A worse preoperative condition and greater number of complications are particularly associated with higher non-medical staffing and operational costs. A similar observation was made in the cost analysis by Lau et al, 10 and explained this by the more extensive surgeries performed in these patients. 9 The latter is reflected in our finding of higher costs associated with slower growing tumors, which is likely to be explained by more aggressive surgeries performed in these patients.…”
Section: Accepted Manuscriptsupporting
confidence: 82%
See 1 more Smart Citation
“…24,25 A worse preoperative condition and greater number of complications are particularly associated with higher non-medical staffing and operational costs. A similar observation was made in the cost analysis by Lau et al, 10 and explained this by the more extensive surgeries performed in these patients. 9 The latter is reflected in our finding of higher costs associated with slower growing tumors, which is likely to be explained by more aggressive surgeries performed in these patients.…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…Several studies have reported costs of surgery for spinal metastases, and figures vary widely: €15,267 for both inpatient care and outpatient follow up in a Belgian study using Diagnosis Related Groups (DRG) codes and national tariffs 8 , an average inpatient cost of £16,885 in a United Kingdom study with patient-level actual costs, 9 but an average of $50,098 for direct costs to the hospital for inpatient stays in a San Francisco study, 10 and an average total of €87,814 over a lifetime horizon in a Danish study. 11 Detailed cost-utility analyses comparing surgical versus non-surgical approaches were performed by three authors.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have discussed healthcare utilization associated with intradural spinal tumors 14,15,24,41 as compared to multiple studies assessing costs in the treatment of metastatic epidural spinal cord compression. [25][26][27]42,43 Sharma et al 14 reported that the mean total hospital charges for treating intramedullary spine tumors in the National Inpatient Sample from 2003 to 2010 was $61 157.…”
Section: Discussionmentioning
confidence: 99%
“…Prior hospitalization of 15 days and lung metastases were independent risk factors for readmission. Another single center study of 181 patients with both primary and metastatic tumors reported an overall perioperative complication rate or 21.0% with 11.9% 90-day readmissions, costing approximately $20,000 each (50). Other factors that may affect complication rates include patient age and location of spinal metastases.…”
Section: Complicationsmentioning
confidence: 99%